2003
DOI: 10.1046/j.1469-0691.2003.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of tuberculosis among Saudi nationals: role of drug resistance and compliance

Abstract: Successful treatment outcome among Saudi Nationals seen at the KKNGH in 1993-99 was below the rate recommended by the WHO, and failed treatment was associated with poor compliance, male gender and drug-resistant Mycobacterium tuberculosis. These results emphasize the importance of culture and sensitivity tests for Mycobacterium tuberculosis and close supervision of patients taking antituberculosis medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…The mean response size for nonSaudis (13.9 +/7 mm) was significantly larger than for Saudis (8.9 +/7 mm, p < 0.001). These data suggest that visitors and immigrants to Saudi Arabia are associated with a higher rate of tuberculosis dis- ease, which is in agreement with data from Europe [37]. Recent report by Ministry of Health showed that TB infection rate has risen again.…”
Section: Epidemiology Of Tb In Saudi Arabiasupporting
confidence: 89%
See 2 more Smart Citations
“…The mean response size for nonSaudis (13.9 +/7 mm) was significantly larger than for Saudis (8.9 +/7 mm, p < 0.001). These data suggest that visitors and immigrants to Saudi Arabia are associated with a higher rate of tuberculosis dis- ease, which is in agreement with data from Europe [37]. Recent report by Ministry of Health showed that TB infection rate has risen again.…”
Section: Epidemiology Of Tb In Saudi Arabiasupporting
confidence: 89%
“…Despite the implementation of the NTP and DOTS, the number of patients effectively treated in Saudi Arabia has fallen below the WHO target of 85% with drug resistance, noncompliance and over the counter access to anti-tuberculosis treatment being contributing factors [5,15,37]. A retrospective study was conducted, which included 147 patients with culture proven diagnosis of tuberculosis seen at the King Khalid National Guard Hospital, Jeddah, between June 1993 and June 1999.…”
Section: National Tuberculosis Program (Ntp) and Directly Observed Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment outcome has never reached the 85% target set by the WHO, despite the implementation of DOTS in the early nineties. The treatment failure or default rate in the country was reported to be very high in previous studies, ranging from 13.23% to 30.6% [42,43]. However, recent nationwide published data is not available to assess the current status.…”
Section: Qualitative Researchmentioning
confidence: 99%
“…Although the TB incidence in Turkey has decreased by half since 1985, several studies have shown the proportion of drugresistant TB cases to be higher than the global average (3,5,10,11,20,24,26). In 2005, Surucuoglu and colleagues reported that the rate of resistance to any anti-TB drugs among 355 isolates of Mycobacterium tuberculosis obtained from western Turkey was 21.1%, while another study found that among the 1,513 TB cases diagnosed in Istanbul, Turkey, in 2005, 19% were resistant to at least one drug (20,25).…”
mentioning
confidence: 99%